Inequality, environmental protection and growth - Laura Marsiliani; T. I. Renström (Fondazione Eni Enrico Mattei (FEEM), 2000)
Why do Scandinavian countries perform better in terms of environmental protection than other European Union countries? In this paper, we explore the hypothesis that societies characterised by low-income inequality (such as the Nordic European countries) generate political-economic equilibria where environmental policy is more stringent. We model an overlapping-generations economy in which individuals differ in skills to address the question to what extent in modern democracies, income distribution influences the stringency of environmental policy and consequently the growth of a country. Individuals work when they are young and own capital when they are old. Pollution externalities are present due to the use of a polluting factor. The government uses the revenue from a capital-income tax and a pollution tax for a lump-sum transfer to the old generation. The fiscal decision at each point in time is taken by a majority elected representative. In politico-economic equilibrium, the lower the skill of the median individual is relative to the average, the smaller the pollution tax and the capital stock are, and the greater the capital income-tax and the relative use of the polluting factor. We perform both steady-state analysis and examine the transition path. Subsequently, we present an empirical analysis for two panels of seven and ten industrialised countries from the late seventies to late nineties. Our framework is able to explain the stylised facts regarding inequality, environmental protection, and growth.
Keywords: D62; D72; E62; H20; 330; Environmental policy; majority voting; endogenous fiscal structure; income distribution; overlapping generations; growth; Umweltschutz; Einkommensverteilung; Overlapping Generations; Wirtschaftswachstum; Theorie